Retroperitoneal Colon Perforation with Review of Retroperitoneal Anatomic Relationships: Case Series with Review of Literature - Satoh, Shina; Hwang, Albert; Berliner, Leonard (Journal of Gastrointestinal and Abdominal Radiology, 2023)
We present two cases of iatrogenic retroperitoneal perforation involving the ascending and descending colon. The unique imaging findings in these two cases demonstrate potential routes of communication for air originating in the retroperitoneum. In context of these cases, we review the clinical presentation, management, and anatomic features of retroperitoneal perforation. Along with clinical history, an understanding of retroperitoneal anatomic relationships can aid radiologists in identifying the origin of perforation.
Keywords: retroperitoneal perforation; pneumoretroperitoneum; computed tomography; radiograph; retroperitoneal anatomy